2019
DOI: 10.3390/cells8050400
|View full text |Cite
|
Sign up to set email alerts
|

NLRX1 Enhances Glutamate Uptake and Inhibits Glutamate Release by Astrocytes

Abstract: Uptake of glutamate from the extracellular space and glutamate release to neurons are two major processes conducted by astrocytes in the central nervous system (CNS) that protect against glutamate excitotoxicity and strengthen neuronal firing, respectively. During inflammatory conditions in the CNS, astrocytes may lose one or both of these functions, resulting in accumulation of the extracellular glutamate, which eventually leads to excitotoxic neuronal death, which in turn worsens the CNS inflammation. NLRX1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 76 publications
0
25
0
Order By: Relevance
“…According to previous knowledge that 17β-estradiol can bind to its own receptor, ERα [48,49,50,51], we determined whether 17β-estradiol activate SIRT1 through ERα dependent and independent manner. Our Western blot and immunofluorescence results showed that d -gal treatment reduce ERα and SIRT1 expression in adult mouse brain (Figure 4a–c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous knowledge that 17β-estradiol can bind to its own receptor, ERα [48,49,50,51], we determined whether 17β-estradiol activate SIRT1 through ERα dependent and independent manner. Our Western blot and immunofluorescence results showed that d -gal treatment reduce ERα and SIRT1 expression in adult mouse brain (Figure 4a–c).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrated that 17β-estradiol can bind to its own receptor, ERα [48,49,50,51]. We determined whether 17β-estradiol can bind to its receptor and then activate SIRT1.…”
Section: Discussionmentioning
confidence: 99%
“…The assay was carried out as described by Shaimaa Mahmoud with slight modifications [ 28 ]. Astrocytes were seeded in a 24-well plate, and after treatments, the cells were washed 2 times with Hank's Balanced Salt Solution (HBSS) containing calcium and magnesium but without phenol (14025134, Gibco).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, Glu entrance also increases the expression of GS, which would increase energy demands, and there-456 fore might promote GLUT-1 mediated glucose up-take 457 (Mendez-Flores et al, 2016;Mahmoud et al, 2019).…”
mentioning
confidence: 99%